PERFORMA PEMILIHAN KOSAKATA BAKU DALAM KOMUNIKASI LISAN OLEH PEJABAT LEGISLATIF DAN TOKOH PARTAI TINGKAT PROVINSI SUMATERA BARAT - Nissaq, Mona Azhari; Ermanto, Ermanto (Universitas Negeri Padang, 2019)
This study aims to explain the choice of vocabulary in language performance and politeness of oral communication by legislative officials and party leaders at level of West Sumatra Province. This type of research is quantitative research with descriptive methods. The research data collecting technique uses documentation and technical notes. The research data analysis techniqueÂ are data classification, data analysis, data interprestation and conclusion. Based on this study, concluded that the choice of vocabulary by legislative officials and party leaders at level of West Sumatra Province is very good. The use of choice of vocabulary in standard vocabulary is 131 data with 87,3% percentage and the use of choice of vocabulary in non-standard vocabulary is 19 data with 12,7% percentage. Researcher found the non-standard vocabulary in two classification. First, non-standard vocabulary in Indonesian language. Second, non-standard vocabulary in foreign language.Keywords: language performance, politeness, legislative officials, standard vocabulary